2001
DOI: 10.1016/s0740-8188(00)00065-7
|View full text |Cite
|
Sign up to set email alerts
|

Information-seeking behavior and use of social science faculty studying stateless nations: a case study

Abstract: The information-seeking behavior of social science faculty studying the Kurds was assessed using a questionnaire, citation analysis, and follow-up inquiry. Two specific questions were addressed: how these faculty locate relevant government information and what factors influence their seeking behavior and use of such information. Results show that besides using traditional methods for locating relevant government information, social science faculty studying the Kurds use the World Wide Web (Web) and electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…This result is noteworthy in that it is consistent with the results of many previous studies (Marouf & Anwar, 2010;Meho & Hass, 2001;Popoola, 2008;De Tiratel, 2000). Previous studies found that authors cited monographs and original sources (Meho & Hass, 2001;Rimmer, Warwick, Blandford, Gow, & Buchanan, 2006;Sherriff, 2010), along with abstracts and indexes, personal correspondence with colleagues, statistical documents, meeting documents, and textbooks (Popoola, 2008).…”
Section: ) Journal Datasupporting
confidence: 88%
“…This result is noteworthy in that it is consistent with the results of many previous studies (Marouf & Anwar, 2010;Meho & Hass, 2001;Popoola, 2008;De Tiratel, 2000). Previous studies found that authors cited monographs and original sources (Meho & Hass, 2001;Rimmer, Warwick, Blandford, Gow, & Buchanan, 2006;Sherriff, 2010), along with abstracts and indexes, personal correspondence with colleagues, statistical documents, meeting documents, and textbooks (Popoola, 2008).…”
Section: ) Journal Datasupporting
confidence: 88%
“…In 1995, in a study on information seeking among social science researchers, Folster (1995) noticed that the study participants had less regard for computer-based services, and preferred books and print journals. Later researchers however, have observed that social science faculty members make wide use of electronic information resources in their research, signifying the impact of information technology in their information behaviour (Shen 2007, Hannah 2005, Meho & Haas 2001, Costa & Meadows 2000. Most of the studies conducted in the social sciences and humanities during this period have similar patterns, showing an inclination towards electronic resources among faculty members.…”
Section: Information Sources Used By the Professoriatementioning
confidence: 97%
“…In a similar study in a law faculty in Ghana, Aforo and Lamptey (2012) observed that faculty members use law reports, law journals and text to seek information, further reinforcing the reliance on print resources than electronic resources by those in the faculty. Meho and Haas (2001), in a study on the information seeking behaviour of social science faculty members studying stateless nations across countries of the USA, United Kingdom, Germany, Canada, Australia, France, Italy, Netherlands, Switzerland and Turkey, showed that besides using traditional methods, social science professors use the World Wide Web and email for locating relevant information, suggesting that these faculty members are aware of and utilise new information technology to support their research. The participants of the study were six assistant professors, nine associate professors and five professors.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Sprecher (2000) considers e-government as a technology to simplify and mechanize transactions between governments and constituents, businesses, or other governments. Also, Meho and Haas (2001) believe that governments should employ new information technologies in order to locate their government information appropriately. Overall, because of the increasing importance of e-government, it is imperative to examine the application of e-government from a range of empirical and theoretical perspectives (Jaeger & Thompson, 2004).…”
Section: Introductionmentioning
confidence: 99%